Ciletuh Geopark Destination Development: Integrating Alternative Food in Hanjeli Tourism Village and Surrounding Destinations - Prawira, Mega Fitriani Adiwarna; Budisetyorini, Beta; Salam, Dicky Arsyul; Adisudharma, Deddy; Wulandari, Wisi (Integrasi Sains Media, 2023)
This study explores integrating alternative food practices into the development of the Ciletuh Geopark Destination, focusing on Hanjeli Tourism Village and its surrounding areas. The research aims to enhance visitor experiences and promote sustainable regional development by blending culinary diversity with tourism offerings. Employing a mixed-methods approach, data was collected through surveys, interviews, and field observations to assess the current state of alternative food integration and its impact on tourism development. Findings reveal significant opportunities for leveraging alternative food as a unique selling point for the destination, catering to diverse visitor preferences and contributing to the socio-economic growth of local communities. The study underscores the importance of strategic planning and collaboration among stakeholders to effectively integrate alternative food practices into destination development initiatives, ensuring the preservation of cultural heritage and environmental sustainability.